Some issues of criminal misconduct in the criminal legislation of the Republic of Kazakhstan - Ongarbayev Е.А.; Balgyntayev А.О. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The article is devoted to the study of topical issues related to the action of criminal misconduct in the legislation of Kazakhstan. The authors analyze the norms of the current criminal legislation, as well as the norms of the draft law, which provides for criminal liability for an unfinished criminal offense. Considering the legislative experience of the neighboring countries, the authors justify the inconsistency of introducing responsibility for the preparation and attempted criminal offense and its inconsistency with the criminal policy in the country. The authors have made a forecast about the possible risks of social tension and other consequences. In addition, the article substantiates the conclusion about the need for a consistent and comprehensive study of the introduced novelties in the legislation.